2=3х-5-7+4х
(3+4)х+(-5-7)=2
7х-12=2
7х=2+12
7х=14
х=14:7
х=2
х = 2
Объяснение:
2 = (3x - 5) - (7 - 4x)
2 = 3х - 5 - 7 + 4х
2 + 5 + 7 = 3х + 4х
14 = 7х
х = 14 : 7
Проверяем:
2 = (3 * 2 - 5) - (7 - 4 * 2)
2 = (6 - 5) - (7 - 8)
2 = 1 - (-1)
2 = 1 + 1
2 = 2
2=3х-5-7+4х
(3+4)х+(-5-7)=2
7х-12=2
7х=2+12
7х=14
х=14:7
х=2
х = 2
Объяснение:
2 = (3x - 5) - (7 - 4x)
2 = 3х - 5 - 7 + 4х
2 + 5 + 7 = 3х + 4х
14 = 7х
х = 14 : 7
х = 2
Проверяем:
2 = (3x - 5) - (7 - 4x)
2 = (3 * 2 - 5) - (7 - 4 * 2)
2 = (6 - 5) - (7 - 8)
2 = 1 - (-1)
2 = 1 + 1
2 = 2